The Process of Becoming a Hatha-Yoga Practitioner - Konecki, Krzysztof T. (Qualitative Sociology Review, 2016)
This paper undertakes the problem of perceiving and feeling the body in the process of acquiring the identity of a hatha-yoga practitioner. The process of becoming a “yogi” is connected with the practice of the work on the body and defining these practices, specific perception of the body, and feeling the body.  Becoming a hatha-yoga practitioner is a process. I describe phases of this process in the paper: 1) The initial phase—constructing motives and first steps; 2) The phase of a fuller recognition of psychophysical effects and ascribing to them appropriate meanings; 3) The phase of a fuller recognition of spiritual aspects of hatha-yoga (quasi-religion). The relations between the mind and the body get complicated at the moment of meaningful engagement in yoga practice and defining body practice as mental practice, as well as spiritual. The work on the body can change the “Western” perspective of defining the body as a material element of human existence (the Cartesian vision) to a vision of treating the body as a spiritualized substance (the vision of Eastern philosophy). Such a change is not always possible if we hold on to the guidelines of other religions as own (e.g., the Catholic religion). Changes in the body and psyche have to be in such a situation defined differently, and also there have to be certain language descriptions of these changes (often acquiring guidelines of set languages formulas) in order to combine the statements of conventional religion with a new spiritual experience.